DYNAMIC CHARACTERISTICS OF THE MAIN INDEXES OF SPACE WEATHER AND THEIR APPLICATION TO THE ANALYSIS MONITORING OBSERVATIONS FLUX DENSITIES OF POWER RADIO SOURCES ON RT <URAN-4> - Guglya, L.; Ryabov, M.; Panishko, S.; Suharev, A. (Одеські астрономічні публікації, 2012)
On radio telescope "URAN-4" of the Odessa observatory of Radio-astronomical Institute during twenty five years (since 1987 till present) monitoring of power galactic and extragalactic radio sources on frequencies 25 and 20MHz has been carried out. Data of the observation was spent in a current of the 22-23th cycles of solar activity and in the beginning of the 24th cycle. Long-term variations density fluxes of radio sources connection with change of a condition of ionosphere in a cycle of solar activity are considered. Means Fourier and Wavelet analysis determine dynamics of changes of the main indexes of space weather and the basic periods of activity are revealed. The obtained data will be used for interpretation of the observation changes flux of radio sources for during all investigated cycle of activity and periods of extreme developments of space weather.